Understanding phosphatidylinositol-3-phosphate dynamics during autophagosome biogenesis - Cebollero, Eduardo (Landes Bioscience, 2012)
Autophagosomes, the hallmark of autophagy, are double-membrane vesicles sequestering cytoplasmic components. They are generated at the phagophore assembly site (PAS), the phagophore being the precursor structure of these carriers. According to the current model, autophagosomes result from the elongation and reorganization of membranes at the PAS/phagophore driven by the concerted action of the autophagy-related (Atg) proteins. Once an autophagosome is completed, the Atg proteins that were associated with the expanding phagophore are released in the cytoplasm and reused for the biogenesis of new vesicles. One molecular event required for autophagosome formation is the generation of phosphatidylinositol 3-phosphate (PtdIns3P) at the PAS. Our data indicate that in addition to the synthesis of this lipid, the dephosphorylation of PtdIns3P is also crucial for autophagy progression. In the absence of Ymr1, a specific PtdIns3P phosphatase and the only yeast member of the myotubularin protein family, Atg proteins remain associated with complete autophagosomes, which are thus unable to fuse with the vacuole.